Animal models for dissecting Vibrio cholerae intestinal pathogenesis and immunity. (February 2022) - Sit, Brandon; Fakoya, Bolutife; Waldor, Matthew K
Highlights: Mammalian, non-mammalian, and invertebrate species are currently used to model Vibrio cholerae pathogenicity. Models vary considerably in their recapitulation of V. cholerae- host interactions in the human intestine. Recent work in animals has revealed molecular details of the host- V. cholerae -microbiome axis. Open areas for investigation include intestinal innate defense against V. cholerae and determinants of cholera transmission. Abstract : The human diarrheal disease cholera is caused by the bacterium Vibrio cholerae . Efforts to develop animal models that closely mimic cholera to study the pathogenesis of this disease began >125 years ago. Here, we review currently used non-surgical, oral inoculation-based animal models for investigation of V. cholerae intestinal colonization and disease and highlight recent discoveries that have illuminated mechanisms of cholera pathogenesis and immunity, particularly in the area of how V. cholerae interacts with the gut microbiome to influence infection. The emergence of high-throughput tools for studies of pathogen–host interactions, along with continued advances in host genetic engineering and manipulation in animal models of V. cholerae will deepen understanding of cholera pathogenesis, uncovering knowledge important for control of this globally important bacterial pathogen.